Development of a Novel Composite Process Measure for Venous Thromboembolism Prophylaxis. Issue 2 (February 2016) - Kinnier, Christine V.; Ju, Mila H.; Kmiecik, Thomas; Barnard, Cindy; Halverson, Terri; Yang, Anthony D.; Caprini, Joseph; Kreutzer, Lindsey; Bilimoria, Karl Y.
Abstract : Background: Postoperative venous thromboembolism (VTE) is important clinically, and VTE quality metrics are used in public reporting and pay-for-performance programs. However, current VTE outcome measures are not valid due to surveillance bias, and the Surgical Care Improvement Project (SCIP-VTE-2) process measure only requires prophylaxis within 24 hours of surgery. Objectives: We sought to (1) develop a novel measure of VTE prophylaxis that requires early ambulation, mechanical prophylaxis, and chemoprophylaxis throughout the hospitalization, and (2) compare hospital performance on the SCIP-VTE-2 process measure to this novel measure. Research Design: A new composite measure of ambulation, sequential compression device (SCD), and chemoprophylaxis component measures was developed. The ambulation component required daily ambulation, the SCD component required documentation of continuous use, and the chemoprophylaxis component required patient-appropriate and medication-appropriate dosing and administration. Requirements could also be met with component-specific exceptions. Surgical patients at an academic center from 2012 to 2013 were assessed for SCIP-VTE-2 and composite measure adherence. Results: Of 786 patients, 589 (74.9%) passed the ambulation measure, 494 (62.8%) passed the SCD measure, and 678 (86.3%) passed the chemoprophylaxis measure. A total of 268 (91.8%) SCD failures and 46 (42.6%) chemoprophylaxis failures were ordered but not administered. When comparing the 2 measures, 784 (99.7%) passed SCIP-VTE-2, whereas only 364 (46.3%) passed the composite measure ( P <0.001). Conclusions: This new measure incorporates the critical aspects of VTE prevention to ensure defect-free care. After additional evaluation, this composite VTE prophylaxis measure with appropriate exclusion criteria may be a better alternative to existing VTE process and outcome measures. Abstract : Supplemental Digital Content is available in the text.